Do political changes aimed at reducing Amazonian deforestation contribute to ecological intensification? - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2015)
Extensive livestock farming was the driver of agricultural colonization and territorial structuring in the Amazon. Since 2008, Amazonian agriculture has been facedwith radical changes in Brazilian policies concerning agricultural land use and the preservation of forest areas. The very viability of livestock systems is threatened and there is thus an urgent need for feasible alternatives to enable the development of sustainable agriculture. Some alternatives are currently being tested by public extension services and private operators. The question is, can these alternatives really be considered as ecological intensification? Defined as ecologically friendly agricultural development, this new trend of intensification aims to reconcile cattle ranching and the protection of Amazon forest ecosystems.Our analysis, based on three contrastedmunicipalities in Pará State, focuses on the points of view of different stakeholders in the livestock sector. Results showthe dominance of classical intensification among the alternatives envisaged, but it is an option that small family farmers cannot easily afford. Alternatives based on land sharing, which promotes agricultural production and environmental preservation on the same areas, are less well known and will require more coordination among local actors.
Fazer mudanças políticas destinadas a reduzir a Amazônia o desmatamento contribui para a intensificação ecológica?
Keywords: Brazil; Amazonia; ecological intensification; livestock raising; family farming; public policy.; CNPQ::CIENCIAS AGRARIAS